123 - MOTOR PERFORMANCE OF SCHOOLCHILDREN IN DIFFERENT NUTRITION STAGES : EVALUATION OF THE PROCESS OF FUNDAMENTAL MOTOR SKILLS, JUMP, KICK AND THROW. (Fiep Bulletin - online, 2011)
This research proposed to examine the motor performance of schoolchildren from 7 to 10 years old in the public school system of Araguaína - To at different nutritional levels. To obtain the nutritional indexes, we adopted the criteria for Warterlow (1976 -1977) using as standard the NCHS reference and the program for evaluation of nutritional status in children (PED2000). Evaluating the motor performance of schoolchildren, in their qualitative aspects, the fundamental patterns of motion were carried out using the matrix analysis of the fundamental patterns of motion proposed by Gallahue (1994). In data analysis, we used descriptive statistics, calculating the mean and standard deviation. The Mann-Whitney test was used to compare groups on qualitative data. The participants were 398 students who were, 47.74% (n = 190) male and 52.26% (n = 208) female, 8.48% of total population. Considering the individual characteristics of nutritional status in relation to motor performance, in this study it was displayed a superior maturation indexes of male students over female ones in all surveyed movements , and superior performance of the movements of students in a nutritional adequacy (eutrophic) situation in the grounds jump and throw, as opposed to fundamental movement kick that was displayed superior maturation indexes of male students at nutritional risk situation and female students in a nutritional disorder situation.
Keywords: Nutritional status; motor development; schoolchildren